Tommaso Campanella in the Schulmetaphysik: The Doctrine of the Three Primalities and the Case of the Lutheran Liborius Capsius (1589–1654) in Erfurt - Lamanna, Marco (Renaissance and Reformation / Renaissance et Réforme, 2016)
Following some recent findings, this essay presents the first known case of the reception of the doctrine of the primalities (power, knowledge, and love) by the Italian Tommaso Campanella within German scholastic philosophy, the so-called Schulmetaphysik. Here, the focus is on the Lutheran Liborius Capsius, the first docent of metaphysics at the University of Erfurt after the interdict by Martin Luther against metaphysics. Through his lectures and the disputations discussed by his students, Capsius shows how the Reformed scholastic philosophy was finally able to receive and integrate Renaissance philosophies (also those of anti-scholastic and anti-Aristotelian provenience). The essay is followed by the transcription of the Rerum transcendentium stud. (1635) by Capsius, in which the reception of the doctrine of the primalities takes place.